VD_FINDINFO Arrêt / 2019 / 160 vom 19. Februar 2019 - VD Tribunal cantonal (2019)
RESTITUTIONEN GÉNÉRAL, GAIN ASSURÉ, PÉRIODE D'ATTENTE, FRAIS DE VOYAGE | 18 al. 1 LACI, 23 al. 1 LACI, 95 al. 1 LACI, 25 LPGA